2012
DOI: 10.1532/hsf98.20111141
|View full text |Cite
|
Sign up to set email alerts
|

Review of a 13-Year Single-Center Experience with Minimally Invasive Direct Coronary Artery Bypass as the Primary Surgical Treatment of Coronary Artery Disease

Abstract: MIDCAB is a safe operation with low postoperative mortality and morbidity. With excellent short-term and long-term results, it is a very good alternative compared to both percutaneous coronary intervention (PCI) and conventional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 31 publications
12
44
0
Order By: Relevance
“…Similar reasons for emergent and planned sternotomy conversions were reported in patients with single-vessel diseases undergoing MIDCAB/endoscopic atraumatic coronary artery bypass (11). Most importantly, the above-mentioned events were easily managed with median sternotomy, which did not influence early or late outcome.…”
Section: Discussionmentioning
confidence: 52%
“…Similar reasons for emergent and planned sternotomy conversions were reported in patients with single-vessel diseases undergoing MIDCAB/endoscopic atraumatic coronary artery bypass (11). Most importantly, the above-mentioned events were easily managed with median sternotomy, which did not influence early or late outcome.…”
Section: Discussionmentioning
confidence: 52%
“…To the best of our knowledge, this is the only pro- Long-term patency of internal mammary arterial grafting and its superiority compared to vein grafts anastomosed to the LAD in terms of survival, freedom from infarction, angina, and repeated revascularization could be observed in various trials (19)(20)(21).…”
Section: Discussionmentioning
confidence: 95%
“…MIDCAB continues to be a popular and well-documented approach for non-sternotomy CABG. Holzhey et al [14] recently reported on a series of 1768 MIDCAB procedures with up to 10 years of follow-up, documenting excellent clinical outcomes with 5-and 10-year survival rates of 88.3 and 76.6%, respectively, and rates of freedom from MACEs of 85.3 and 70.9% at 5 and 10 years, respectively. In comparison, our study had 5-and 10-year survival rates of 90.6 and 72.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%